Bahasa Inggris - Mellisa Mellisa; Deri Hendriawan; Atep Sujana; Encep Supriatna (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to analyze the ISPS owned by 4th-grade students at one of the Public Elementary Schools in Cilegon City, in the subject of IPAS on the five senses material. This study used a quantitative descriptive method whose sample consisted of 5 male students and 9 female students. The instrument used was a written test in the form of an essay consisting of 5 questions to measure students' science process skills. The results of the study showed that students' SPS was still low, as evidenced by the average test score of 51, which means the results of this study still indicate low abilities in ISPS. This study identified that integrated science process skills in grade 4 students are still low. These findings provide insight to teachers to design science learning activities that can actively involve students in learning activities. Thus, it is necessary to implement a learning model based on inquiry so that students can be actively involved in learning making learning more meaningful.